Advertising : 50 real-life projects uncovered. - Hickey, Lisa, ....- (Gloucester : Rockport, 2002)
This is the fourth title in the Design Secrets series. Each design project selected is shown in detail from concept to completion including all the steps in-between. This book presents 50 real-life design projects: original plans, sketches, interim drawings, and presentations each accompanied by informative captions that show how designers present their ideas, and solve problems. Each campaign in this book will have one distinctive and creative element that sets it apart and makes it worthwhile to look at closely. For example, one campaign will go into detail about how the creative team came up with the idea; another will go into more detail on the use of a song in the campaign, and how that came to be; and another will address a television campaign that relied heavily on special effects.
Keywords: Adverteren; Reclame